2017
DOI: 10.1097/mpg.0000000000001584
|View full text |Cite
|
Sign up to set email alerts
|

Combination Steroid and Test‐based Food Elimination for Eosinophilic Esophagitis

Abstract: Objectives: Eosinophilic esophagitis (EoE) is a clinicopathologic disorder characterized by infiltration of eosinophils into the esophagus. Primary treatment approaches include topical corticosteroids and/or food elimination. The aim of the present study was to compare the effectiveness of combination therapy (topical corticosteroid plus test-based food elimination [FS]) with single therapy (topical corticosteroid [S] or test-based food elimination [F]). Methods: Chart review of patients with EoE at Texas Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Dual therapy with corticosteroid and elimination diet may be more effective in achieving clinical and histologic remission in some patients but has not been tested in a randomized, prospective manner. 76 In a retrospective study, combination therapy with topical corticosteroid, either swallowed aerosolized fluticasone or oral viscous budesonide, and TFED excluding only milk and soy for 3 months, followed by monotherapy with TFED only for 3 additional months, achieved clinical remission with reduction in dysphagia. 77 However, histologic remission after 3 months of combined dual therapy was lost after corticosteroid discontinuation.…”
Section: Combination Therapy For Eoementioning
confidence: 99%
“…Dual therapy with corticosteroid and elimination diet may be more effective in achieving clinical and histologic remission in some patients but has not been tested in a randomized, prospective manner. 76 In a retrospective study, combination therapy with topical corticosteroid, either swallowed aerosolized fluticasone or oral viscous budesonide, and TFED excluding only milk and soy for 3 months, followed by monotherapy with TFED only for 3 additional months, achieved clinical remission with reduction in dysphagia. 77 However, histologic remission after 3 months of combined dual therapy was lost after corticosteroid discontinuation.…”
Section: Combination Therapy For Eoementioning
confidence: 99%
“…When possible, patients should be maintained on monotherapy to avoid risk of lack of compliance due to therapeutic complexity, add unnecessary cost and side‐effects . If monotherapy fails, a combination therapy with steroids and food avoidance or food avoidance and PPI is acceptable . Short courses of oral/systemic steroids or oesophageal dilations have also been used for short‐term control of the disease …”
Section: Clinical Manifestation Of Eoe and Management Of Eoementioning
confidence: 99%
“…Studies showed that the combination of topical steroids with diet elimination is not superior to single treatment in achieving clinical or histological remission. However, combination therapy could be effective in patients who have previously failed single-agent therapy [54].…”
Section: Treatmentmentioning
confidence: 99%